What type of FDI is attracted by bilateral investment treaties? - Liesbeth Colen; Damiaan Persyn; Andrea Guariso (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
Developing countries have increasingly engaged in Bilateral Investment Treaties (BITs) to attract foreign investors. While it is found that BITs are successful in attracting FDI, we argue that the effectiveness of BITs depends on the type of FDI. We find the effect of BITs to differ importantly across sectors of investment. FDI characterized by higher sunk investment costs responds more strongly to the signing of BITs. Given that the development impact of FDI differs according to the sector of investment, our results raise concerns on the effectiveness of BITs in attracting FDI in those sectors where it is considered most beneficial.
Keywords: 330; investment treaties; foreign direct investment; sunk costs; Central and Eastern Europe; development